Pengembangan Media Jelita Sebagai Sarana Eksplorasi Peristiwa Ikonik Umar bin Khattab pada Siswa Sekolah Dasar - nisa nurpasa (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2026)
This study aims to develop and test the feasibility and effectiveness of JELITA (Jelajah Lini Masa Kalender Hijriyah) media as a historical exploration tool capable of enhancing cognitive understanding and the internalization of moral values (ibrah) of the Khulafaur Rasyidin, specifically regarding Umar bin Khattab for 6th-grade elementary students. The method used is Research and Development (R&D) applying the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research and trials were conducted on 22 6th-grade students at SDN Baginda 1. Validation results from material and media experts indicated that the JELITA media falls into the